LEADERSHIP STYLE PREFERENCES AMONG EXECUTIVE AND LEGISLATIVE ORGANIZATION STUDENTS OF STATE UNIVERSITY OF JAKARTA - Annisa Oktavyana (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
The styles of leadership exemplified in higher educational organizations has an important role to play in organizational success or failure. The development of leadership style and organizational skills of students can be achieved through student organizations. The study aimed at understanding gender differences in leadership style preferences and the influence of residential background on leadership style preference.  It was conducted among 20 students (7 males and 13 females) from Executive and Legislative Organization Students of State University of Jakarta. The primary data was collected through online questionnaire. The questions were adapted from Introduction to leadership: Concepts and practice by Northouse, P. G. It was analyzed using descriptive and cross-sectional method. The results will be presented in tables and chart. It revealed that there was significant gender difference on leadership style. It was seen that more preference for democratic leadership. Based on gender, and males also indicated preference for democratic leadership than authoritarian or laissez-faire leadership style. The students from rural and urban areas didn’t show any differences in their leadership preferences. The complete results have been explained along with the existing theories and literature.